OPTIMIZATION OF BREWING WASTE’S (TRUB) PHENOLIC COMPOUNDS EXTRACTION BY ULTRASOUND ASSISTED USING RESPONSE SURFACE METHODOLOGY - Bianca C. G. Gandolpho; Aline R. Almeida; Gabriel M. Gandolpho; Daniele Z. Freitas; Otávio C. Gasparini; Michelle H. Machado; Pedro L. M. Barreto (Química Nova, 2021)
The brewing waste, also known as trub, is an abundant by-product of the brewing industry. Such material presents high levels of phenolic compounds, which promote antioxidant, antimicrobial and antifungal effects, turning the trub economically attractive. In this study, the trub’s phenolic compounds were extracted by ultrasound-assisted extraction technology. Such experiments were conducted according to a central composite rotatable design (CCRD), with the evaluated parameters being ethanol concentration, solid-liquid ratio and extraction temperature. Response surface methodology (RSM) described the effect of process’ variables through second order polynomial models, adjusted appropriately for such analysis, and optimized the operating conditions, aiming to obtain the maximum extraction of phenolic compounds through the proposed technique. The extraction’s optimal conditions for the evaluated variables were ethanol concentration of 58%, solid-liquid ratio of 1 g per 32 mL, and extraction temperature of 36 ºC, during a 30 minute process. Considering such experimental conditions, the total amount of phenolic compounds was equal to 7.23 mg of gallic acid g-1 trub, indicating that a great concentration of phenolic compounds can be extracted from this material through the proposed technique. Thus, this indicates that trub might be a promising by-product that can be used in different industrial fields.